Pyloric web : Management of a neglected case of Gastric Outlet Obstruction - Agarwal, Nishant; Kumar, Tarun; Kanneganti, Pujana; Verma, Anju; Kumar, Basant (Indian Journal of Child Health, 2024)
Pyloric atresia is an extremely rare cause of gastric outlet obstruction, constituting approximately 1% of all gastrointestinal atresias and occurring in about 1 in 100,000 live births. It is equally prevalent in males and females and may exhibit autosomal recessive inheritance. Clinically, it presents during infancy with non-bilious vomiting, abdominal distension, and failure to thrive. Type 1 pyloric atresia, characterized by a pyloric membrane with an opening, is exceptionally rare and may present later in childhood. We reported the case of a 5-year-old male with the history of recurrent non-bilious vomiting since the age of one year, which worsened over the preceding four months. Examination revealed visible peristalsis and upper abdominal fullness. Radiological findings suggested gastric outlet obstruction, and exploratory laparotomy confirmed Type 1 pyloric atresia. Surgical management involved excision of the pyloric web and Heineke-Mikulicz pyloroplasty. The child had an uneventful recovery and demonstrated significant improvement in weight and nutritional status at a 6-month follow-up. The diagnosis of pyloric atresia is challenging due to its rarity and similarity to other conditions like duodenal atresia or hypertrophic pyloric stenosis. Early diagnosis through clinical suspicion, radiological evaluation, and definitive surgical intervention is crucial to prevent complications such as aspiration pneumonia and metabolic imbalances. This case highlights the importance of considering pyloric atresia in children with recurrent vomiting and failure to thrive, even beyond infancy, and emphasizes the significance of prompt surgical management for favorable outcomes.